2019
DOI: 10.1108/qrfm-12-2018-0131
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion and FinTech

Abstract: Purpose Using data from World Bank and Global Islamic Finance Report, this paper aims to compare the performance of countries following Islamic and conventional finance system in terms of financial inclusion and FinTech. Design/methodology/approach Ten countries from both financial systems have been selected based on the presence of Islamic finance and conventional finance in the country. Data was analyzed from year 2011 to 2017 and keeping the former as base year to measure the change in the population frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…The growing impact of the fintech sector depends on technological innovation [13], as well as on combining the innovative processes with the creation and delivery of customized, 24/7 financial services that enhance customer experience [14]. Fintech means not only service innovation, but also innovation of financial business models [15][16][17]. Fintech companies are more technology-oriented than traditional counterparts; with the help of information technologies, financial services can be offered to customers in a faster and more convenient way and at lower costs [2,18].…”
Section: Introductionmentioning
confidence: 99%
“…The growing impact of the fintech sector depends on technological innovation [13], as well as on combining the innovative processes with the creation and delivery of customized, 24/7 financial services that enhance customer experience [14]. Fintech means not only service innovation, but also innovation of financial business models [15][16][17]. Fintech companies are more technology-oriented than traditional counterparts; with the help of information technologies, financial services can be offered to customers in a faster and more convenient way and at lower costs [2,18].…”
Section: Introductionmentioning
confidence: 99%
“… 11 Wasiuzzaman et al [ 68 ] Creditworthiness and access to finance of SMEs in Malaysia: do linkages with large firms matter? 10 Bongomin et al [ 69 ] Microfinance accessibility, social cohesion, and survival of women MSMEs in post-war communities in sub-Saharan Africa: Lessons from Northern Uganda 8 Shahriar et al [ 70 ] Gender differences in the repayment of microcredit: The mediating role of trustworthiness 7 Koh [ 71 ] The impact of microfinance services on socioeconomic welfare of urban vulnerable households in Malaysia 2 Mittal and Raman [ 72 ] Financing woes: estimating the impact of MSME financing gap on financial structure practices of firm owners 2 Cluster 5: Islamic financial inclusion Pomeroy et al [ 73 ] Financial inclusion to build economic resilience in small-scale fisheries 20 Ali et al [ 74 ] Islamic financial inclusion determinants in Indonesia: an ANP approach 12 Zauro et al [ 75 ] Enhancing socioeconomic justice and financial inclusion in Nigeria: The role of Zakat, Sadaqah, and Qardhul Hassan 8 Raza et al [ 76 ] Determining the nexus between financial inclusion and economic development in Pakistan 8 Baber [ 77 ] Financial inclusion and FinTech: A comparative study of countries following Islamic finance and conventional finance 5 Khmous and Besim [ 78 ] Impact of Islamic banking share on financial inclusion: evidence from MENA 3 ...…”
Section: Resultsmentioning
confidence: 99%
“…This construct discusses financial inclusion through Islamic Fin-tech. Literature suggested that Pakistan occupies low rank in financial inclusion when compared to regional and global standards (Baber, 2019). Most of the respondents believe that Fin-tech is a good tool to promote financial inclusion as people get maximum services through online channels.…”
Section: Promotion Of Financial Inclusion Through Fintechmentioning
confidence: 99%